PENGARUH ROA, ROE, EPS DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR KONSUMEN NON-SIKLIS - Hasibuan, Ervina Rosarina; Yunita, Rizki Arvi; Husnasari, Khalila (Politeknik Bisnis Indonesia, 2025)
ABSTRACT This study aims to examine how return on assets (ROA), return on equity (ROE), earnings per share (EPS), and firm size influence stock prices. The research focuses on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. A purposive sampling method was employed, resulting in a sample of 34 entities. Conducted over a three-year period, the study encompasses a total of 102 data. Secondary data utilized includes annual financial statements and stock price information obtained from idx.co.id. Data analysis was performed using multiple linear regression techniques with SPSS version 27. The findings indicate that, individually, ROA, ROE, and firm size do not significantly affect stock prices in the non-cyclical consumer sector listed on the IDX during 2022–2024. However, EPS has a significant positive impact on stock prices within the same sector and period. Collectively, the variables ROA, ROE, EPS, and firm size are able to explain variations in stock price. Keywords: ROA, ROE, EPS, firm size, stock price